Reconstructing Islamic Legal Ethics : The Role of Maqāṣid al-Sharīʿah in Contemporary Muslim Community Governance - Ludfi Ludfi; Rinovian Rais (International Forum of Researchers and Lecturers, 2024)
This research explores the role of Maqāṣid al-Sharīʿah in modern governance systems, focusing on its application to contemporary issues in Muslim-majority societies. The study examines the challenges posed by traditional Islamic jurisprudence and its rigidity in addressing evolving social, political, and economic conditions. Specifically, it aims to assess how Maqāṣid al-Sharīʿah can enhance governance by promoting justice, public welfare, and the protection of rights, as well as offering an adaptable framework for legal reforms. The research employs a comparative literature review and thematic analysis, examining classical and contemporary texts to identify key themes related to the integration of Maqāṣid into governance. The main findings suggest that Maqāṣid al-Sharīʿah provides a more flexible and responsive legal framework compared to traditional textual fiqh, especially in the context of modern governance challenges such as human rights, social justice, and public welfare. The study concludes that integrating Maqāṣid principles into contemporary Islamic governance can lead to more equitable and effective systems, enhancing social cohesion, economic stability, and the protection of human rights. Future research could explore specific case studies of Maqāṣid implementation in various governance contexts to further understand its practical applications.